(untitled) (Development Service Industry Management, 2025)
The main purpose of the article is to study the evolution of theoretical and methodological approaches to transfer pricing in the context of marketing. In the context of constant economic transformation and technological changes, pricing processes are also undergoing changes under the influence of a number of economic, in particular globalization, factors. Therefore, there is a need for a comprehensive scientific analysis of changes in approaches to transfer pricing and in determining the globalization influences that shape its modern foundations. The research methodology is based on a combination of general philosophical, special and interdisciplinary methods, as well as key scientific approaches - systemic, process and situational. Among the general scientific tools, analysis and synthesis were used to study the impact of globalization trends on changing the concept of transfer pricing in the marketing system. The method of theoretical generalization was used to classify the globalization factors that shape this concept The scientific novelty of the obtained results lies in the substantiation and proof that transfer pricing in the context of globalization acquires the fundamental features of a marketing approach to pricing. It is proved that methodological approaches to transfer pricing belong to the group of marketing pricing methods. The practical significance of the of the research results is the analysis of practical approaches to the use of transfer pricing methods and the formation of an economic mechanism for transfer pricing as part of marketing pricing policy. Generalization of the transfer pricing methodology, taking into account the methods of its legislative regulation.